The source a novel - Michener, James A. (James Albert) 1907-1997 (Random House, 1965)
An archaeological excavation of Tell Makor launches a journey into the history and culture of the Jews that includes the early Hebrews, the impact of Christianity, the Spanish Inquisition, and the modern Middle East conflict.